Many Hypotheses LAO Testing With Rejection of Decision for Arbitrarily Varying Object - Haroutunian, Evgueni; Hakobyan , Parandzem; Yessayan, Aram (Mathematical Problems of Computer Science, 2021)
The model of multiple statistical hypotheses testing with possibility rejecting to make choices between hypotheses concerning discrete arbitrarily varying object is investigated. The optimal procedure of decisions is shown. The matrix of optimal asymptotical interdependencies (reliability-reliability functions) of all possible pairs of the error probability exponents (reliabilities) is studied for arbitrarily varying object with the current states sequence known to the statistician.